TS-PINN: a dual-branch physics-informed neural network based on two-source theory for evapotranspiration estimation - Xing Rong; Chunlin Huang; Feinan Xu; Jinliang Hou; Peng Dou; Ying Zhang; Qiang Bie; Tianwen Feng; Zhihua Zhang (Journal of Hydrology, 2026)

Carbon dot-based catalytic materials: From photo/electrocatalysis to nanozyme activity - Pei-De Zhu; Chang Liu; Hui Wang; Rong-Yu Yao; Ling-Rui Sun; Xin-Ru Xu; Jing-Wen Jiang; Ying-Sheng Xu; Kun-Peng Lin; Jia-Xing Wu (Journal of Environmental Chemical Engineering, 2026)

Arginine-rich hemp seed globulin-tannic acid non-covalent complexation: Structural compaction, enhanced antioxidant/emulsifying properties, and modulated digestibility - Yu Zhang; Xiao-Dong Tian; Zuo-Xing Di; Hai-Bo Jin; Guang-Xiang He; Suo-He Yang; Rong-Yue Zhang; Lei Ma; Xiao-Yan Guo; Peng-Wei Xu (Food Chemistry, 2026)

Structural remodeling of myofibrillar protein by Mesona blumes polysaccharide: Effects on multi-scale structure and functional properties - Wenjie Wang; Xueqing Zhang; Chenxi Xing; Lu Peng; Rong Xu; Hao Wang; Aijun Hu; Lulu Chu (Food Chemistry, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Three new diterpenoids from the aerial parts of Callicarpa macrophylla - Liang Gou; Rong-Shuai Li; Jian-Lin Lai; Yan-Mei Ning; Xue-Ting Ji; Xiong Qiu; Chao Peng; Xiao-Li Li; Xing-Jie Zhang; Wei-Lie Xiao (Natural Product Research, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Efficient production of medium-chain fatty acids in engineered Escherichia coli strains from ionic liquids pretreated bamboo enzymatic hydrolysate with carbon dioxide fixation - Ling Zhou; Kun Rong; Kai-Xing Xiao; Ruo-Shi Luo; Zhao Qin; Rustam Iqra; Xia Fang; Jikai Zong; Zhiyao Peng; Min Long; Dan Wang (Bioresource Technology, 2026)

Advances in natural products with anti-skin photoaging: mechanisms, phytochemical diversity, and therapeutic potential - Yi Luo; Xiao-Cui Liu; Yu-Jie Li; Yu-Jia Wang; Ming-Hua Qiu; Xing-Rong Peng (Phytochemistry Reviews, 2026)

Glutamine-hydrolyzing GMP Synthase Gene (guaA) Regulates Siderophore Synthesis in the Nitrogen-fixing Bacterium (NFB) Kosakonia radicincitans GXGL-4A - Er-Xing Wang; Bao-Yun Feng; Ya-Ting Zhang; Meng-Ting Zhang; Lu-Rong Xu; Yan-Wen Xue; Yun-Peng Chen (Current Microbiology, 2026)

Four new phenolic constituents from root barks of Paeonia ostii - Qian-Qian Meng; Yi Su; Shun-Yao Tong; Xing-Rong Peng; Jun-Chen Zhu; Ji-Kai Liu (Natural Product Research, 2025)

Cultivation of Auxenochlorella protothecoides using tofu whey wastewater for aquaculture feed production: Integrating resource recovery and microalgal biomass valorization strategy - Liang Zhong; Xing Meng; Yulong Zhang; Zongfan Peng; Rong Zhou; Yufang Tang; Yuqin Li (Bioresource Technology, 2025)

Two pairs of novel isochromanone derivatives with antiadipogenic effects from the cultures of Ganoderma gibbosum - Yu-Jie Li; Xiao-Cui Liu; Yi Luo; Ming-Hua Qiu; Ping Zhao; Xing-Rong Peng (Phytochemistry Letters, 2025)

Efficacy and safety of an mRNA encoding neutralizing antibody against SARS-CoV-2 in non-human primates - Hang Chi; Suo-Qun Zhao; Yun-Peng Liu; Xiao-Chuan Xiong; Xia Zhong; Xing-Xing Suo; Xing-Yao Huang; Can Yue; Jing-Jing Zhang; Zhe Cong; Na Li; Fei-Xue Du; et al. (Science Bulletin, 2025)

Novel galactose-rich polysaccharide from Ganoderma lucidum: structural characterization and immunomodulatory activities - Zhou-Wei Wu; Xiao-Cui Liu; Chen-Xi Quan; Xin-Yu Tao; Yi-Luo; Xue-Fang Zhao; Xing-Rong Peng; Ming-Hua Qiu (Carbohydrate Polymers, 2025)

Constructing asymmetric D′-A-D" imine covalent organic frameworks to optimize exciton effect and enhance photocatalytic reduction of U(VI) - Yang-Xing He; Xiao-Juan Chen; Rui Zhang; Hao-Xuan He; Cheng-Peng Niu; Cheng-Rong Zhang; Zhi-Hai Peng; Yuan-Jun Cai; Zhen-Wen Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Epilimnetic oligotrophication increases contribution of oxic methane production to atmospheric methane flux from stratified lakes - Fan Xun; Muhua Feng; Cheng Zhao; Wenlei Luo; Xiaotong Han; Zhen Ci; Yifan Yin; Rong Wang; Qinglong L. Wu; Hans-Peter Grossart; Peng Xing (Water Research, 2025)

Influence of Influent Load on Nitrification/Denitrification with MBBR for Oil Shale Retorting Wastewater Treatment: Performance and Microbial Community Structure - Rong-xin Zhang; Yi Liu; Dian-nan Huang; Li Zhang; Xing-guan Ma; Peng-fei Yu; Chuang Liu; Yong-yong Wang (Water, Air, & Soil Pollution, 2025)

Tuning local charge polarization of covalent organic frameworks for enhanced photocatalytic uranium (VI) reduction - Xiao-Xing Wang; Cheng-Rong Zhang; Rui-Xiang Bi; Zhi-Hai Peng; Hao-Xuan He; Rui Zhang; An-Min Song; Jia-Xin Qi; Xiao-Juan Chen; Xin Liu; Yuan-Jun Cai; Ru-Ping Liang; et al. (Chemical Engineering Journal, 2024)

Impact of a Potent Strain of Plant Growth-Promoting Bacteria (PGPB), Bacillus subtilis S1 on Bacterial Community Composition, Enzymatic Activity, and Nitrogen Content in Cucumber Rhizosphere Soils - Meng-Ting Zhang; Yu-Qing Bao; Bao-Yun Feng; Lu-Rong Xu; Ya-Ting Zhang; Er-Xing Wang; Yun-Peng Chen (Current Microbiology, 2024)

A novel hollow flower shaped Cu9S8 antibacterial agent for removing sulfonamide in water environment: effects of composite with magnetic biochar, differential adsorption, and mechanism study - Rui-peng Li; Zheng-rong Hu; Xing Wang; Jun Chen; Qing-qing Liu; Ying Zhao; Zhong-bao Zhao; Xu-lin Lu; Zhi-wei Zhang (Environmental Science and Pollution Research, 2024)

Lensless shadow microscopy-based shortcut analysis strategy for fast quantification of microplastic fibers released to water - Yu Su; Chenqi Yang; Yao Peng; Cheng Yang; Yanhua Wang; Yong Wang; Feng Yan; Baoshan Xing; Rong Ji (Water Research, 2024)

Intestinal microbiota via NLRP3 inflammasome dependent neuronal pyroptosis mediates anxiety-like behaviour in mice exposed to 3.5 GHz radiofrequency radiation - Gui-qiang Zhou; Xing Wang; Peng Gao; Tong-zhou Qin; Ling Guo; Zhao-wen Zhang; Zhi-fei Huang; Jia-jin Lin; Yun-tao Jing; Hao-nan Wang; Chun-ping Wang; Gui-rong Ding (Science of The Total Environment, 2024)

ZnO nanorod coatings attenuate antibiotic resistance genes (ARGs) on their surface biofilms in estuarine environment - Xing-pan Guo; Rong-rong Sha; Yu-cen Wang; Jia Yan; Bo Peng; Zuo-shun Niu; Wen-liang Liu; Xin Li; Yi Yang (Journal of Environmental Chemical Engineering, 2024)

Phosphorylated covalent organic framework/graphene composites for photoelectrothermal integrated collaborative reduction of uranium - Rui Zhang; Liang Tao; Cheng-Peng Niu; Cheng-Rong Zhang; Tie-Ying Shi; Xiao-Xing Wang; Ying-Ao Wang; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

Steam disinfection enhances bioaccessibility of metallic nanoparticles in nano-enabled silicone-rubber baby bottle teats, pacifiers, and teethers - Yu Su; Bin Wang; Xin Tong; Shuchuan Peng; Sijin Liu; Baoshan Xing; Rong Ji (Journal of Environmental Sciences, 2024)

Toxicity of common biocides used in aquaculture to embryos and larvae of Brachymystax tsinlingensis Li - Xing‐chen Guo; Zhi‐peng Chu; Rong‐qun Song; Zhen‐lu Wang; Rui‐jiao Li; Dong‐mei Xiong; Mu‐zi Zhang; Hai‐bo Jiang; Jian Shao (Journal of Fish Biology, 2024)
Brachymystax tsinlingensis Li is a threatened fish species endemic to China. With the problems of environmental factors and seeding breeding diseases, it is important to further improve the efficiency of seeding breeding and the basis of resource protection. This study investigated the acute toxicity of copper, zinc and methylene blue (MB) on hatching, survival, morphology, heart rate (HR) and stress behaviour of B. tsinlingensis . Eggs (diameter: 3.86 ± 0.07 mm, weight: 0.032 ± 0.004 g) of B. tsinlingensis were selected randomly from artificial propagation and developed from eye‐pigmentation‐stage embryos to yolk‐sac stage larvae (length: 12.40 ± 0.02 mm, weight: 0.03 ± 0.001 g) and exposed to different concentrations of Cu, Zn and MB for 144 h in a series of semi‐static toxicity tests. The acute toxicity tests indicated that the 96‐h median lethal concentration (LC 50 ) values of the embryos and larvae were 1.71 and 0.22 mg l −1 for copper and 2.57 and 2.72 mg l −1 for zinc, respectively, whereas the MB LC 50 after 144‐h exposure for embryos and larvae were 67.88 and 17.81 mg l −1 , respectively. The safe concentrations of copper, zinc and MB were 0.17, 0.77 and 6.79 mg l −1 for embryos and 0.03, 0.03 and 1.78 mg l −1 for larvae, respectively. Copper, zinc and MB treatments with concentrations greater than 1.60, 2.00 and 60.00 mg l −1 , respectively, led to a significantly low hatching rate and significantly high embryo mortality ( P −1 led to significantly high larvae mortality ( P P P B. tsinlingensis embryos or larvae might be more resistant to copper, zinc and MB than other members of the Salmonidae family, which benefits their resource protection and restoration.

An updated review of the genus Rhododendron since 2010: Traditional uses, phytochemistry, and pharmacology - Xing-Jian Liu; Hai-Guo Su; Xing-Rong Peng; Hui-Chang Bi; Ming-Hua Qiu (Phytochemistry, 2024)

Biochar establishing syntrophic partnership between exoelectrogens to facilitate extracellular electron transfer - Gaojun Wang; Lu Chen; Yao Xing; Changxi Sun; Peng Fu; Qian Li; Rong Chen (Science of The Total Environment, 2023)

Serum levels of IL-6/IL-10/GLDH may be early recognition markers of anti-tuberculosis drugs (ATB) -induced liver injury - Huai-Rong Xiang; Yun Li; Xuan Cheng; Bei He; Hua-Min Li; Qi-Zhi Zhang; Bin Wang; Wen-Xing Peng (Toxicology and Applied Pharmacology, 2023)

Flavonoid glycosides from the nectar of Camellia reticulata Lindl. - Xin-Lan Chen; Xing-Rong Peng; Xue-Yang Gong; Yi-Qiu Liu; Zhuo Qing; Xiao-Xiao Ren; Rui Su; Li-Ming Fang; Ming-Hua Qiu; Kun Dong (Natural Product Research, 2022)

Quantitative Proteomics Analysis of Sugarcane Ratoon Crop Chlorosis - Ye-Geng Fan; Rong-Fa Chen; Li-Hang Qiu; Zhong-Feng Zhou; Hui-Wen Zhou; Ji-Guang Wei; Xiu-Peng Song; Ting Luo; Prakash Lakshmanan; Xing Huang; Jian-Ming Wu; Yang-Rui Li (Sugar Tech, 2021)

Construction and characterization of UAA-controlled recombinant Zika virus by genetic code expansion - Rong-Rong Zhang; Qing Ye; Xiao-Feng Li; Yong-Qiang Deng; Yan-Peng Xu; Xing-Yao Huang; Qing Xia; Cheng-Feng Qin (Science China Life Sciences, 2021)

Mid–Late Cretaceous igneous activity in South China: the Qianjia example, Hainan Island - Sai-Jun Sun; Li-Peng Zhang; Rong-Qing Zhang; Xing Ding; Hong-Li Zhu; Zhao-Feng Zhang; Wei-Dong Sun (International Geology Review, 2018)

ApoA-I induces S1P release from endothelial cells through ABCA1 and SR-BI in a positive feedback manner - Xing Liu; Kun Ren; Rong Suo; Sheng-Lin Xiong; Qing-Hai Zhang; Zhong-Cheng Mo; Zhen-Li Tang; Yue Jiang; Xiao-Shan Peng; Guang-Hui Yi (Journal of Physiology and Biochemistry, 2016)

Experimental research on seismoelectric effects in sandstone - Rong Peng; Jian-Xing Wei; Bang-Rang Di; Pin-Bo Ding; Zi-Chun Liu (Applied Geophysics, 2016)

Improving the antioxidant activity and enriching salvianolic acids by the fermentation of Salvia miltiorrhizae with Geomyces luteus - Yun Xing; Le Cai; Tian-peng Yin; Yang Chen; Jing Yu; Ya-rong Wang; Zhong-tao Ding (Journal of Zhejiang University-SCIENCE B, 2016)

MiR-219 Protects Against Seizure in the Kainic Acid Model of Epilepsy - Honghua Zheng; Rong Tang; Yi Yao; Zhilin Ji; Yuanyuan Cao; Zhaoji Liu; Feng Peng; Wenjie Wang; Dan Can; Huiqin Xing; Guojun Bu; Huaxi Xu; et al. (Molecular Neurobiology, 2016)

New cytotoxic and anti-inflammatory compounds isolated from Morus alba L. - Jing Qin; Min Fan; Juan He; Xing-De Wu; Li-Yan Peng; Jia Su; Xiao Cheng; Yan Li; Ling-Mei Kong; Rong-Tao Li; Qin-Shi Zhao (Natural Product Research, 2015)

Effects of Plant Stress Signal Molecules on the Production of Wilforgine in an Endophytic Actinomycete Isolated from Tripterygium wilfordii Hook.f. - Guo-peng Miao; Chuan-shu Zhu; Jun-tao Feng; Li-rong Han; Xing Zhang (Current Microbiology, 2015)

Synthesis, biological evaluation, and molecular docking studies of pyrazolyl-acylhydrazone derivatives as novel anticancer agents - Man Xing; Ting-Ting Zhao; Yu-Jia Ren; Na-Na Peng; Xian-Hui Yang; Xi Li; Hui Zhang; Gao-Qi Liu; Li-Rong Zhang; Hai-Liang Zhu (Medicinal Chemistry Research, 2014)

A new phenolic glycoside from the stems of Hydnocarpus hainanensis - Hai-Ming Shi; Zhi-Rong Yao; Xing-Yun Chai; Zheng-Ren Xu; Yu-Hong Zhou; Jing Wen; Peng-Fei Tu (Natural Product Research, 2008)

Unexpected effect of concomitantly administered curcumin on the pharmacokinetics of talinolol in healthy Chinese volunteers - He Juan; Bernd Terhaag; Zang Cong; Zhang Bi-Kui; Zhu Rong-Hua; Wang Feng; Su Fen-Li; Song Juan; Tang Jing; Peng Wen-Xing (European Journal of Clinical Pharmacology, 2007)

Proteomic analysis of the serum in patients with idiopathic pulmonary arterial hypertension - Min Yu; Xing-xiang Wang; Fu-rong Zhang; Yun-peng Shang; Yu-xi Du; Hong-juan Chen; Jun-zhu Chen (Journal of Zhejiang University-SCIENCE B, 2007)